Faculty experiences and perspectives of teaching standardised nursing language to nursing students: an ethnographic research study - Kristi Rannus; Dickon Weir-Hughes (Proceedings of the Estonian Academy of Sciences)
Despite advancements in health care, the implementation of the NNN system â standardised nursing language incorporating NANDA-I diagnoses, NOC outcomes, and NIC interventions â within Estoniaâs health information system has been slow. Studies across various healthcare settings reveal persistent gaps in nursing documentation, compounded by limited technological support and inadequate backing from colleagues and leadership. These issues compromise patient care quality, service continuity, and information sharing among healthcare professionals.